Alternative Polyadenylation of Tumor Suppressor Genes in Small Intestinal Neuroendocrine Tumors - Rehfeld, Anders; Plass, Mireya; Døssing, Kristina; Knigge, Ulrich; Kjær, Andreas; Krogh, Anders; Friis-Hansen, Lennart (Frontiers in Endocrinology, 2014)
The tumorigenesis of small intestinal neuroendocrine tumors is poorly understood. Recent studies have associated alternative polyadenylation with proliferation, cell transformation and cancer. Polyadenylation is the process in which the pre-mRNA is cleaved at a polyA site and a polyA tail is added. Genes with two or more polyA sites can undergo alternative polyadenylation. This produces two or more distinct mRNA isoforms with different 3’ untranslated regions. Additionally, alternative polyadenylation can also produce mRNAs containing different 3’-terminal coding regions. Therefore, alternative polyadenylation alters both the repertoire and the expression level of proteins. Here we used high-throughput sequencing data to map polyA sites and characterize polyadenylation genome-wide in three small intestinal neuroendocrine tumors and a reference sample. In the tumors sixteen genes showed significant changes of alternative polyadenylation pattern, which lead to either the 3’ truncation of mRNA coding regions or 3’ untranslated regions. Among these, 11 genes had been previously associated with cancer, with 4 genes being known tumor suppressors: DCC, PDZD2, MAGI1 and DACT2. We validated the alternative polyadenylation in 3 out of 3 cases with Q-RT-PCR. Our findings suggest that changes of alternative polyadenylation pattern in these 16 genes could be involved in the tumorigenesis of small intestinal neuroendocrine tumors. Furthermore, they also point to alternative polyadenylation as a new target for both diagnostic and treatment of small intestinal neuroendocrine tumors. The identified genes with alternative polyadenylation specific to the small intestinal neuroendocrine tumors could be further tested as diagnostic markers and drug targets for disease prevention and treatment.